A New Heuristic Algorithm for Multiobjective Bulk Transportation Problem - Singh, Sukhveer (My University, 2011)
The classical transportation problem (TP) is one of the many well-structured problems in operations research that has been extensively studied in literature. The TP is one of the subclass of the linear programming problems for which simple and practical computational procedures have been developed that take the advantage of the special structure of the problem. The TP is amongst the most important special linear programming problem – in terms of the frequency with it appears in the applications and also in the simplicity of the procedure developed for its solutions. Transportation problem has been paid much attention and classified into several types of transmutations and one of the variants of the TP is bulk transportation problem (BTP) which differs from the TP that it stipulates that the total requirement of each destination has to be met from single source only, however a some source can supply to any number of destination subject to the availability of the commodity at the source. The present thesis consists of three chapters. Chapter one is introducing in nature in which multi-objective optimization has been described and brief survey of the literature to the topic has been discussed. In the second chapter two algorithms for multi-objective bulk transportation problem (MBTP) given by Prakash et al. (2007, 2009) have been reviewed. In chapter three, a heuristic algorithm has been developed for MBTP which is a combination the algorithms review in chapter second
Msc, SMCA
Keywords: Multiobjective Bulk Transportation Problem; Efficient or non-dominated SOM